Helminthiasis prevalence in brick makers at Lambada Peukan Village, Aceh Besar Region, Indonesia - Dedy Syahrizal; Cut Mustika; . Ikhsan; Mulkan Azhary (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Helminthiasis are the common health problem in the develop country. WHO prediction  400 million people had infection of helminthiasis. Soil is the usual media to transmitted helminth to human (soil transmitted helminthiasis). One of the rule worker that has hard contact  to helminth is the brick maker. This activity usual doing with convensional technique.The objective of  this devotion are to knowing helminthiasis prevalence on brick maker in Lambada Peukan Village. The primer data is the count of helminthiasis that get from feces examination in laboratory. This result overgo to promotive, preventive and curative activity.The helminthiasis prevalence in Lambada Peukan is 37,5%. To resolve this problem we doing the preventive and curative activity with giving albendazole preparat and Ferrum. Beside that we also make education activity to the workers. The aim of this activity is to increase need and ability of  the worker  to maintance from helminthiasis. The workers who in participated in this programme had having positive response that they want  to participated in all off this programme.